Using Challenge Educational Technology to Increase Students' Vocabulary - Muqaddas Egamberdieva; Kamilova Okhista (International Journal on Integrated Education, 2022)
In this article, the importance of using modern methods in teaching of English language and literature at schools and the issue of creating a problematic situation based on contrasting and comparing language phenomena with the use of problematic educational technologies in teaching English today are widely covered.